Nondestructive assessment of quality of Nanfeng mandarin fruit by a portable near infrared spectroscopy - Xudong, Sun; Hailiang, Zhang; Yande, Liu (International Journal of Agricultural and Biological Engineering, 2009)
A portable near infrared spectroscopy system was developed for assessing the quality of Nanfeng mandarin fruit. One hundred and fifty-three Nanfeng mandarin samples were used to measure the performance of the system. Several pretreatment methods were adopted to process the spectra. Then Support Vector Machine (SVM), Back Propagation Neural Network (BPNN) and Partial Least Square (PLS) were used to build models for soluble solids content (SSC), titratable acidity (TA), vitamin C and surface color. The best results were obtained by SVM. The correlation coefficient (R) and root mean square error of prediction (RMSEP) were (0.93, 0.65°Brix), (0.66, 0.09%), (0.81, 2.7mg/100g) and (0.57, 0.81) for SSC, TA, vitamin C and color, respectively. The results demonstrated that the portable near infrared spectroscopy was feasible for determining the Nanfeng mandarin quality nondestructively. Keywords: Portable near infrared spectroscopy, SVM, Nanfeng mandarin fruit, SSC, TA, Vitamin C, surface color DOI: 10.3965/j.issn.1934-6344.2009.01.065-071 Citation: Sun Xudong, Zhang Hailiang, Liu Yande. Nondestructive assessment of quality of Nanfeng mandarin fruit by a portable near infrared spectroscopy. Int J Agric & Biol Eng, 2009; 2(1): 65